Drug-loaded liposome-capped mesoporous core–shell magnetic nanoparticles for cellular toxicity study. (November 2016) - Sharifabad, Maneea Eizadi; Mercer, Tim; Sen, Tapas
Liposome-capped core–shell mesoporous silica-coated superparamagnetic iron oxide nanoparticles called 'magnetic protocells' were prepared as novel nanocomposites and used for loading anticancer drug doxorubicin (DOX) for cellular toxicity study. Cytotoxicity of the magnetic protocells with or without DOX was tested in vitro on commercial MCF7 and U87 cell lines under alternating magnetic field. MCF7 cell line treated with the DOX-loaded nanoparticles under alternating magnetic field exhibited nearly 20% lower survival rate after 24 h compared with cells treated with free DOX and similarly, it was around 24% when applied to U87. The results indicate that the magnetic protocells could be useful for future cancer treatment in vivo by the combination of targeted drug delivery and magnetic hyperthermia.